Experimental study on the wave-induced dynamic response and hydrodynamic characteristics of a submerged floating tunnel with elastically truncated boundary condition. (March 2023) - Yang, Zhiwen; Li, Jinzhao; Xu, Yuwang; Ji, Xinran; Sun, Zhenxiang; Ouyang, Qunan; Zhang, Huaqing
Abstract: Hydrodynamic load and motion response are the first considerations in the structural design of a submerged floating tunnel (SFT). Currently, most of the relevant studies have been based on a two-dimensional model test with a fixed or fully free boundary condition, which inhibits a deep investigation of the hydrodynamic characteristics with an elastic constraint. As a result, a series of difficulties exist in the structural design and analysis of an SFT. In this study, an SFT model with a one-degree-of-freedom vertical elastically truncated boundary condition was established to investigate the motion response and hydrodynamic characteristics of the tube under the wave action. The effect of several typical hydrodynamic parameters, such as the buoyancy-weight ratio, γ, the relative frequency, f / f N, the Keulegan–Carpenter (KC) number, the reduced velocity, U r, the Reynolds number, Re, and the generalized Ursells number, on the motion characteristics of the tube, were selectively analyzed, and the reverse feedback mechanism from the tube's motion response to the hydrodynamic loads was confirmed. Finally, the critical hydrodynamic parameters corresponding to the maximum motion response at different values of γ were obtained, and a formula for calculating the hydrodynamic load parameters of the SFT in the motion state was established. The main conclusions of this study are as follows: (i) Under the wave action, the motion of the SFT shows an apparent nonlinearity, which is mainly caused by the intensive interaction between the tube and its surrounding water particles, as well as the nonlinearity of the wave. (ii) The relative displacement of the tube first increases and then decreases with increasing values of f / f N, U r, KC number, Re, and the generalized Ursells number. (iii) γ is inversely proportional to the maximum relative displacement of the tube and the wave force on the tube in its motion direction. (iv) Under the motion boundary condition (as opposed to the fixed boundary condition), the peak frequency of the wave force on the SFT in its motion direction decreases and approaches the natural vibration frequency of the tube, whereas the wave force perpendicular to the motion direction increases. When the incident wave frequency is close to the natural vibration frequency of the tube, the tube resonates easily, leading to an increased wave force in the motion direction. (v) If the velocity in the Morison equation is substituted by the water particle velocity measured when the tube is at its equilibrium position, the inertia coefficient in the motion direction of the tube is linearly related to its displacement, whereas that in the direction perpendicular to the motion direction is logarithmically related to its displacement. Highlights: A 1-DOF elastically truncated experiment was carried out to investigate the motion response and hydrodynamic characteristics of the tube under the wave action. Selectively analyzed the effect of several typical hydrodynamic parameters on the motion characteristics of the tube. Confirmed the reverse feedback mechanism from the motion response of the tube to the hydrodynamic loads. Established a formula for calculating the hydrodynamic load parameters of the SFT in the motion state.